If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = -2x + 4 Reorder the terms: 9 = 4 + -2x Solving 9 = 4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 9 + 2x = 4 + -2x + 2x Combine like terms: -2x + 2x = 0 9 + 2x = 4 + 0 9 + 2x = 4 Add '-9' to each side of the equation. 9 + -9 + 2x = 4 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = 4 + -9 2x = 4 + -9 Combine like terms: 4 + -9 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5
| 7(p+1)=p-9 | | C=3.14(5) | | -5/6f+1=-4 | | 12-2A-2B=0 | | 5+-26=18x | | 2=15x | | (x+8)(x-3)+30=0 | | 52=4x-4 | | -4/6f+1=-4 | | 7u+9u+u=140 | | 7y-2=13+10 | | 4z-2=2+7 | | 4x-9=6r-13 | | 7x=5x-18 | | 9mn+p=2k | | 10/2+1=6 | | -8(x+9)=-96 | | b^2+6b-x^2+9=0 | | 5=4x+4 | | p/2+1=6 | | -91=-7(x+2) | | 6x+20=34 | | -2y-7=-13 | | 7b+12=31b | | 4(-0.4+-0.29)-3y=-13 | | 8x+22=-28 | | -6x+(7x+2)-(x-9)=19 | | |3x-8|-|3x-2|=6 | | 44-3x=8-9x | | 9x+1=8x+2 | | 11+(2-9x)=15-(2x+9) | | -11=6b+5b |